Use of low concentrations of hydrogen peroxide in extracting gold from metallurgically complex gold ores - Feldmann, Robert Max Werner (Curtin University, 2016)
The study was to understand the fundamentals of benefits hydrogen peroxide has shown in cyanide leaching of complex, gold bearing ores. The understanding was gathered by a comprehensive literature review followed by laboratory experiments including leach experiments, electrochemical studies, several analytical methodologies and statistical data analysis.